Pengaruh Pengawasan dan Motivasi Kerja Terhadap Disiplin Kerja Guru dan Pegawai di SDN 21 Kota Bima - Fita Aprianti; Amirulmukminin Amirulmukminin; Firmansyah Kusumayadi (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
of the Bima College of Economics (STIE) This study aims to analyze the influence of supervision and work motivation on the work discipline of teachers and employees at SDN 21 Bima City. The research method used is a quantitative method with a survey approach. Data was collected through a questionnaire distributed to teachers and employees at SDN 21 Bima City. The results of the study show that supervision has a significant influence on work discipline, where effective supervision can improve the discipline of teachers and employees. In addition, work motivation was also found to have a significant positive impact on work discipline. The combination of good supervision and high work motivation has been shown to improve the overall level of work discipline. These findings have important implications for school management in an effort to improve work discipline through effective supervision and work motivation.